Healing plants in the spiritual landscape of the Shanhai jing (Itineraries of mountains and seas, comp. 1st c. BC) - Dorofeeva-Lichtmann, Vera (Circumscribere International Journal for the History of Science, 2015)
In this paper I advance arguments against studies of plants listed in the Shanhai jing山海經 (Itineraries of mountains and seas, compiled about the 1st century BC) in terms of materia medica or systematic botany. I propose to consider them instead as an integral part of an ideal organisation of terrestrial space conveyed by this early Chinese work – a spiritual landscape. The latter belongs to a so-called ‘totalistic’ conception, simultaneously embracing cosmological, religious, political, topographical and other dimensions, which cannot be disaggregated, as they are part of a single, complexly interrelated whole. The main distortion to be avoided is to regard its features, for instance the healing plants, independently from other dimensions, and in terms of typologically different or modernistic conceptual frameworks.